Chemotherapy‐induced toxicity in patients with testicular germ cell tumors: The impact of physical fitness and regular exercise. (19th July 2021) - Amiri, Ali; Chovanec, Michal; Oliva, Viktor; Sedliak, Milan; Mego, Michal; Ukropec, Jozef; Ukropcová, Barbara
Abstract: Background: Testicular germ cell tumors (TGCTs) represent ∼95% of testicular malignancies and are the most common type of malignancy in young male adults. While the incidence of TGCTs has increased during the last decades, the advances in treatment, namely introducing cisplatin into the chemotherapy regimen, have made TGCTs highly curable with the 10‐year survival rate exceeding 95%. However, in parallel with increased cure rates, survivors may experience acute and late adverse effects of treatment, which increase morbidity, reduce the quality of life, and can be potentially life‐threatening. Chemotherapy‐related toxicities include cardiovascular and metabolic diseases, secondary cancer, avascular necrosis, cognitive impairment, cancer‐related fatigue, poor mental health‐related quality of life, nephrotoxicity, hypogonadism, neurotoxicity, pulmonary toxicity, anxiety, and depression. These treatment‐related adverse effects have emerged as important survivorship dilemmas in TGCT cancer survivors. Recently, regular physical exercise has increasingly attracted research and clinical attention as an adjunct therapy for cancer patients. Purpose: Herein, we review the most common chemotherapy‐related adverse effects in TGCT survivors and clinical relevance of exercise and increased cardio‐respiratory fitness in modulating chemotherapy‐related toxicity and quality of life in this population. Results and conclusion: Exercise has positive effects on a spectrum of physical and psychosocial outcomes during and after cancer treatment, and current guidelines on exercise prescription in chronic diseases define the recommended dose (volume and intensity) of regular exercise for cancer survivors, highlighting regular, sufficiently intensive physical activity as an essential part of patients' care.